Intellectual Capital Disclosure in the Lens of Corporate Governance: The Role of Firm Age and Size - Nurjanah, Rina; Yahya, Adibah; Mulyanto, Heru (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study examines the effects of company size, age, and ownership concentration on Intellectual Capital Disclosure (ICD) in manufacturing firms listed on the Indonesia Stock Exchange. Using quantitative methods and secondary data from annual reports, the findings indicate that company size and age do not significantly affect ICD. Furthermore, ownership concentration does not act as a moderating variable. These results imply that ownership structure and stakeholder pressure are more influential in shaping disclosure practices. Consequently, companies should enhance governance and transparency in their intellectual capital reporting to better align with stakeholder expectations.